2023
DOI: 10.3390/ijerph20032088
|View full text |Cite
|
Sign up to set email alerts
|

The Incremental Role of Multiorgan Point-of-Care Ultrasounds in the Emergency Setting

Abstract: Point-of-care ultrasonography (POCUS) represents a goal-directed ultrasound examination performed by clinicians directly involved in patient healthcare. POCUS has been widely used in emergency departments, where US exams allow physicians to make quick diagnoses and to recognize early life-threatening conditions which require prompt interventions. Although initially meant for the real-time evaluation of cardiovascular and respiratory pathologies, its use has been extended to a wide range of clinical application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 149 publications
0
4
0
Order By: Relevance
“…Recent developments in computerized diagnostic algorithms for ECG interpretation, particularly useful in pre-hospital environments, have assisted ECG interpretations [ 16 ]. Computer ECG measurements are instantaneous, eliminate human bias, and can accurately measure waveforms with high resolution.…”
Section: The Optimal Management Of Patients Rushed To the Cardiac Cat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in computerized diagnostic algorithms for ECG interpretation, particularly useful in pre-hospital environments, have assisted ECG interpretations [ 16 ]. Computer ECG measurements are instantaneous, eliminate human bias, and can accurately measure waveforms with high resolution.…”
Section: The Optimal Management Of Patients Rushed To the Cardiac Cat...mentioning
confidence: 99%
“…The high sensitivity and specificity of the ECG in diagnosing STEMI are presupposed to avoid unnecessary and potentially dangerous invasive examinations or delaying the diagnosis of an alternative pathology to STEMI due to symptoms and ECG changes. Recent developments in computerized diagnostic algorithms for ECG interpretation, particularly useful in pre-hospital environments, have assisted ECG interpretations [16].…”
Section: The Optimal Management Of Patients Rushed To the Cardiac Cat...mentioning
confidence: 99%
“…Gastric ultrasound is increasingly used to assess gastric emptying in anesthesia and intensive care [33–35]. Some development is also reported in point-of-care ultrasound assessment of certain intestinal pathologies and abdominal venous congestion [36,37]. One study reported assessment of enteral feeding intolerance with measuring gastric antrum, colonic diameter and peristaltic frequency [38], while standardized protocol for gastrointestinal ultrasound in critical illness is still lacking [39].…”
Section: Assessment Of Gastrointestinal Function During Critical Illnessmentioning
confidence: 99%
“…However, although the ratio between the right and left ventricles [4] and the TAPSE index are the most studied signs for their prognostic value [5], the prognostic role of each sign of RV dysfunction is not clear [6][7][8]. Moreover, there is little evidence relating to the predictive capacity of other echocardiographic parameters commonly evaluated in the Emergency Department (ED) [9], such as the ejection fraction of the left ventricle and systolic pulmonary arterial pressure (sPAP) [10]. Finally, signs of RV dysfunction have a debated role in terms of sensitivity and specificity, considering high-sensitivity troponin [11,12].…”
Section: Introductionmentioning
confidence: 99%